Preschoolers’ Induction of the Concept of Material Kind to Make Predictions: The Effects of Comparison and Linguistic Labels - Hardy, Ilonca; Saalbach, Henrik; Leuchter, Miriam; Schalk, Lennart (Frontiers in Psychology, 2020)
Inductive reasoning is fundamental for scientific reasoning. Analogical reasoning by comparison is considered a special case of inductive reasoning, allowing learners to induce underlying commonalities of several entities, thereby decreasing the salience of the objects’ common superficial, perceptual features (e.g., Namy & Gentner, 2002). In the present research, we tested whether task environments aimed to trigger analogical reasoning by comparison will support preschoolers’ induction of the concept of material kind for predicting and explaining objects’ floating and sinking as a central aspect of scientific reasoning. In two experiments, we tested whether the number of presented objects consisting of a specific material (one versus two standards) and the labelling of objects with the respective material name would benefit preschoolers’ material-based inferences. In each item set, we asked the children (N=158 in both studies) to predict an object’s floating and sinking matching the standard(s) and to verbally explain their selections. As expected, we found a significant effect for the number of standards in both experiments on the prediction task, suggesting that children successfully induced the relevance of material kind due to comparison. However, labels did not additionally increase the effect of standards. Furthermore, we found a general transfer of conceptual knowledge; however, this was not associated with the task conditions. Our findings suggest that tasks inviting analogical reasoning by comparison with two standards are useful for promoting young children’s hypothesis generation.